A bioeconomic analysis of the potential of seaweed Hypnea pseudomusciformis farming to different targeted markets - Pereira, Stefany A. [UNESP]; Kimpara, Janaina M.; Valenti, Wagner C. [UNESP] (Taylor & Francis, 2020)
Simulations were performed to evaluate the economic potential of farming the seaweed Hypnea pseudomusciformis in two production scales for the carrageenan, human food, and glycolic extract markets in Brazil. The initial investment was low in all scenarios (US$25,579 in 7.5 ha and US$71,202 in 22.5 ha farms). Labor and taxes were the major production costs for production commercialized for the carrageenan and human food markets, respectively. Liquid glycerin and bottles were the main costs when the productions were marketed for glycolic extract. The carrageenan market showed no economic feasibility. On the other hand, the human consumption market was shown as very profitable, resilient, and highly attractive (IRR was ∼100%). Marketing the glycolic extract is also feasible and attractive (IRR was ∼25%) but had lower economic indicators and low resilience when compared to the human food market scenario. Upscaling the production optimized investments and reduced production costs, improving profitability. The plasticity of seaweed enables entrepreneurs to explore different markets simultaneously to increase farm resilience.
Keywords: carrageenan; cosmetics; functional food; Macroalgae; nutraceuticals